Collaboration Opportunities : Engaging NGOs in Driving Best Practices in Library and Information Service Delivery in Nigerian Libraries - Osuchukwu, Ngozi Perpetua; Otubelu, Nnenna Blessing; Ogbonna, Uchenna Andrew; Ndukwe, Nkeiruka Caroline (MiddleBelt Journal of Library and Information Science, 2016)
This paper highlighted the significance of fostering synergy between libraries and non-governmental organizations (NGOs); as both are interconnected in improving and developing our society, through essential services that revolve around creation, dissemination, and storage of information. This study was conducted in Anambra State purposely to identify NGOs and their activities, find out libraries that have collaborated with NGOs, establish whether NGOs and librarians can actually work together and find out challenges involved in collaboration. The population was 42 respondents made up of 29 NGOs officials and 13 librarians. These are NGO personnel partnering with the researcher’s information center and the public librarians in Anambra State Library Board. Interview and focused group discussions were used in data collection. The study was a quantitative research and as such, the design was analyzed using calibrated formulae. Tables were used to show the findings which indicated that there are wide opportunities and great need for librarians to collaborate with NGOs. The findings further showed that only public library and its librarians have real collaboration with NGOs, although other librarians are willing to collaborate, depending on their areas of needs. Thus, one of the recommendations is that librarians should get focused with the collaboration trend so as to offer qualitative services to their users. This is because NGO interactions can integrate librarians more into project management and create space for the dynamic interplay between the libraries and their clients.